Thermal Dynamics in Optical Networks: Analyzing Spectral Bandwidth Reduction and Signal Distortion - Mohammed, Abdulrazak A.; QasMarrogy, Ghassan A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
The signal distribution of any fiber-optic network system is an important factor in optical communication, which determines the quality of the optical signal transmission. One of the important effects is the temperature degrees; that effect is on the main parameters of optical communication (of which the fiber optic is the main part). The main material in fiber optics is glass. And as is well known, temperature has a strong effect on the glass, especially the core of fiber optics, because the structure of fiber optics contains several glass layers with different refractive indexes. Hence, in the present article, the effect of temperature on the optical signal and other components of the optical network system has been analyzed and studied. The analysis includes aberration, dispersion, and distortion of the optical network communication signal. The result has been discussed and analyzed for variables in the BW of the spectral when the temperature changed.